Analisis jenis batuan menggunakan metoda geolistrik tahanan jenis konfigurasi wenner di Bukit Apit Puhun Kecamatan Guguk Panjang Kota Bukittinggi (Analysis of rock types using the geoelectric resistivity method of the Wenner configuration at Apit Puhun Hill, Guguk Panjang District, Bukittinggi City) - Mia Azhari (Department of Physics – Universitas Negeri Padang UNP, 2016)
Bukit apit puhun located in West Sumatera traversed by active segment of sumatera named Sianok Segment. This condition cause Bukit Apit Puhun prone to earthquake. Erathquake caused the layer composition of earth changed. Based on this condition, rock structure research in Bukit Apit Puhun must be done. The research is basic research descriptively. Exploration was collected by resistivity Geoelectrical method wenner configuration. Wenner configuration had a good vertical resolution and suitable for mapping rocks structure. The interpretation of the data was used Smoothness-Constraint Least Squares inversion to get resistivity and depth of rocks in 2D model cross section below the earth surface. Result of this research indicated the type of rocks in Bukit Apit Puhun were Clay, Sandstone, Limestone, Andesite, and Granite. Total distribution area of rocks that build Bukit Apit Puhun in five track that is Clay consists of 6.452,48 m2, Sandstone 16.988,28 m2, Limestone 40.661,39 m2, Andesite 8.951,72 m2, and Granite 7.919,08 m2. Based on this calculation, was found that Bukit Apit Puhun dominated by Limestone